Variability of cork from Portuguese Quercus suber studied by solid-state 13C-NMR and FTIR spectroscopies (Biopolymers, 2001)
A new approach is presented for the study of the variability of Portuguese reproduction cork using solid-state 13C-NMR spectroscopy and photoacoustic (PAS) FTIR (FTIR-PAS) spectroscopy combined with chemometrics. Cork samples were collected from 12 different geographical sites, and their 13C-cross-polarization with magic angle spinning (CP/MAS) and FTIR spectra were registered. A large spectral variability among the cork samples was detected by principal component analysis and found to relate to the suberin and carbohydrate contents. This variability was independent of the sample geographical origin but significantly dependent on the cork quality, thus enabling the distinction of cork samples according to the latter property. The suberin content of the cork samples was predicted using multivariate regression models based on the 13C-NMR and FTIR spectra of the samples as reported previously. Finally, the relationship between the variability of the 13C-CP/MAS spectra with that of the FTIR-PAS spectra was studied by outer product analysis. This type of multivariate analysis enabled a clear correlation to be established between the peaks assigned to suberin and carbohydrate in the FTIR spectrum and those appearing in the 13C-CP/MAS spectra. © 2001 John Wiley & Sons, Inc. Biopolymers (Biospectroscopy) 62: 268–277, 2001
The following values have no corresponding Zotero field: publisher: John Wiley & Sons, Inc.